Reduction of biofilm formation of Escherichia coli by targeting quorum sensing and adhesion genes using the CRISPR/Cas9-HDR approach, and its clinical application on urinary catheter - Maryam Alshammari; Aldossary Ahmad; Manal AlKhulaifi; Dunia Al Farraj; Samar Alsudir; Moahmed Alarawi; Gojobori Takashi; Essam Alyamani (Elsevier, 2023)
Background: Escherichia coli is a common cause of biofilm-associated urinary tract infections (UTIs). Bioﬁlm formation in E. coli is responsible for various indwelling medical device-associated infections, including catheter-associated urinary tract infections (CAUTIs). This study aimed to reduce bioﬁlm formation of E. coli ATCC 25922 by knocking out genes involved in quorum sensing (QS) (luxS) and adhesion (fimH and bolA) using the CRISPR/Cas9-HDR approach. Method: Single-guide RNAs (sgRNAs) were designed to target luxS, fimH and bolA genes. Donor DNA for homologous recombination was constructed to provide accurate repairs of double-strand breaks (DSBs). A biofilm quantification assay (crystal violet assay) was performed to quantify the biofilm formation of mutant and wild-type strains. Morphological changes in biofilm architecture were confirmed by scanning electron microscopy (SEM). Further application of the biofilm formation of mutant and wild-type strains on urinary catheter was tested. Results: Crystal violet assay showed that the biofilm formation of ΔfimH, ΔluxS, and ΔbolA strains was significantly reduced compared to the wild-type strain (P value<0.001). The percentage of biofilm reduction of mutant strains was as follows: ΔluxS1 77.51 %, ΔfimH1 78.37 %, ΔfimH2 84.17 %, ΔbolA1 78.24 %, and ΔbolA2 75.39 %. Microscopic analysis showed that all mutant strains lack extracellular polymeric substances (EPS) production compared to the wild-type strain, which was embedded in its EPS matrix. The adherence, cell aggregation, and biofilm formation of wild-type strain on urinary catheters were significantly higher compared to ΔfimH, ΔluxS and ΔbolA strains. Conclusion: Altogether, our results demonstrated that the knockout of luxS, fimH, and bolA genes reduced EPS matrix production, which is considered the main factor in the development, maturation, and maintenance of the integrity of biofilm. This pathway could be a potential strategy to disrupt E. coli biofilm-associated UTIs. This study suggests that CRISPR/Cas9-HDR system may provide an efficient and site-specific gene editing approach that exhibits a possible antibiofilm strategy through intervention with the QS mechanism and adhesion property to suppress biofilm formation associated with UTI catheter infections.